(untitled) (Fiep Bulletin - online, 2020)
The practice of activities focused on flexibility aims to maintain and improve this valence, with benefits of improving physical fitness and aiming to make children and adults in future healthier and well-being. School physical education classes are more conducive environments for inserting these exercises for children, especially those in the phase of body modification, where we can highlight the final years of elementary school. Emphasizing the importance of the physical education professional as a mediator of this learning, adding specific classes of flexibility work showing in conceptual procedure a theory about importance, benefits, types, exercises on physical flexibility and other procedural part with the practice properly divided to a Lesson plan, which is divided into warm-up, development and back to calm. Based on the theoretical framework, the authors consider flexibility an essential physical capacity in motor device functionality, thus indicating the relationship of flexibility as an improvement in quality of life and well-being, which is said to be its relationship with health.